CAPM applications for appropriate stock pricing – impact of speculation companies - Urbański, Stanisław; Skalna, Iwona (Managerial Economics, 2018)
Research on the pricing of stocks listed on the Polish market shows a contradiction with the classic CAPM. The results of these studies are consistent with the results carried out on other developed markets. The reasons for inconsistent pricing are not known; this is the main objective of thiswork. It is a continuation of the authors’ previous work on the impact of speculation and penny stocks on the pricing in light of the ICAPM. Despite the scientific justifications for pricing in light of the ICAPM, a common estimate of the capital cost for companies is still performed on the basisof the classic CAPM. It has been conjectured that speculative stocks contribute to incompatible pricing in light of the CAPM. The elimination of speculative stocks would allow for the proper estimate of the cost of capital without the need of complicated and laborious ICAPM applications. The research is conducted on the basis of stocks listed on the Warsaw Stock Exchange from 1995through 2012. The tested period is divided into two separate sub-periods: 1995–2005 (the years preceding Poland’s accession to the EU) and 2005–12 (the years of Poland’s membership in the EU). The analyzed stocks are grouped into quintile portfolios according to two variants. Thepricing tests are carried out in three modes. In Mode, 1 all listed stocks are analyzed. In Modes 2 and 3, speculative stocks are excluded from the study. The research results prove the validity of the adopted conjectures.